1995
DOI: 10.1002/jcla.1860090613
|View full text |Cite
|
Sign up to set email alerts
|

Expression of urokinase‐type plasminogen activator and plasminogen activator inhibitor in colon disease

Abstract: Surveillance colonoscopy and biopsy are inaccurate methods of predicting the likelihood of ulcerative colitis patients to develop colon carcinoma. We examined uPA and PAI-1 as potential markers for assessing these patients and those with familial polyposis who are at risk of developing colon cancer. For comparison, biopsies of normal colon and Crohn's disease were evaluated. We examined 77 colonic mucosa specimens taken from patients undergoing elective resection for benign and malignant colonic disease. uPA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…These reports indicated that H. pylori infection may play a role in destruction of the extracellular matrix. uPA and uPAR are reportedly produced by the cancer cells and stromal cells in several types of human tumors in vivo and in vitro [9–12], and play an important role in the process of degradation of the extracellular matrix [4–6]. The secreted uPA binds to uPAR on the cell membrane of some types of cells to restrict the uPA activity to the cell surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…These reports indicated that H. pylori infection may play a role in destruction of the extracellular matrix. uPA and uPAR are reportedly produced by the cancer cells and stromal cells in several types of human tumors in vivo and in vitro [9–12], and play an important role in the process of degradation of the extracellular matrix [4–6]. The secreted uPA binds to uPAR on the cell membrane of some types of cells to restrict the uPA activity to the cell surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies indicate that MMP-9 and uPAR expression in tumour-associated lymphocytes, macrophages and neutrophils are inversely associated with invasion and metastasis [41] . It is also reported that inflammatory conditions in the colon is associated with an increased uPA expression [42,43] . These observations could also in part explain the findings in the present study, as tumourassociated lymphocytes are suspected to exert anticancer effects [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Besides MMP-3 and MMP-9 are markedly up-regulated in intestinal fistulae, that may contribute to fistula formation and perpetuation through degradation of the extracellular matrix [43]. Moreover, both uPA and plasminogen activator inhibitor; (PAI-1) expressions are significantly higher in IBD patients than in controls [44]. uPA and plasmin, in addition to their role in fibrinolysis and activation of pro-MMPs, have been shown to be an intracellular signal transducer through specific receptors Therefore, the uPA/ plasmin system has been shown to play an important role in pathological angiogenesis.…”
Section: Activation Of the Angiogenic Process And Loss Of Quiescence mentioning
confidence: 99%